2015
DOI: 10.1111/ane.12410
|View full text |Cite
|
Sign up to set email alerts
|

Long-term subarachnoid haemorrhage survivors still die due to cerebrovascular causes

Abstract: Long-term subarachnoid haemorrhage survivors still die due to cerebrovascular causes Lindgren C, S€ oderberg S, Koskinen L-OD, Hultin M, Edvardsson L, Naredi S. Long-term subarachnoid haemorrhage survivors still die due to cerebrovascular causes. Acta Neurol Scand 2015: 132: 410-416.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 35 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Diabetes could be a contributing factor to the long-term vascular mortality in some cases. Earlier publications have shown that SAH patients have an increased mortality due to cerebrovascular disorders [ 10 , 9 ]. The influence of previous stroke on mortality has not been addressed before, but this finding suggests that SAH may be part of a more systemic vascular disorder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes could be a contributing factor to the long-term vascular mortality in some cases. Earlier publications have shown that SAH patients have an increased mortality due to cerebrovascular disorders [ 10 , 9 ]. The influence of previous stroke on mortality has not been addressed before, but this finding suggests that SAH may be part of a more systemic vascular disorder.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies on the cause of death after the acute phase, and in the short term, this correlated to cardiovascular incidents [ 11 ]. In the long term, mortality correlated with cerebrovascular disorders [ 10 ]. However, there are few or no studies on the impact of the earlier health and lifestyle on the mortality after SAH.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that more than 25% of patients with aSAH died in the hospital, and more than 40% have persistent neurological deficits 2 . Moreover, patients who survive the initial haemorrhage are susceptible to cerebrovascular diseases and have mortality rates that exceed the general population 3,4 . For example, the recurrence of aSAH in survivors was estimated to be 15‐times higher than that in the general population.…”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, patients who survive the initial haemorrhage are susceptible to cerebrovascular diseases and have mortality rates that exceed the general population. 3,4 For example, the recurrence of aSAH in survivors was estimated to be 15-times higher than that in the general population. Thus, it is critical to recognize the cellular and molecular differences between aneurysmal tissues from aSAH patients and normal intracranial arterial tissues, which could offer a theoretical basis for the high recurrence of cerebrovascular disease in patients with aSAH.Inflammatory reactions are involved in the formation, progression and deterioration of aSAH.…”
mentioning
confidence: 99%
“…Aneurysmal subarachnoid hemorrhage (SAH) is a disease that affects the patient's prognosis with various complications even after clipping or coiling (1). aSAH activates a robust complement response exacerbating cell death and eventually leading to dysfunction of the blood-brain barrier (2, 3).…”
Section: Introductionmentioning
confidence: 99%